Pengaruh Konsentrasi Asam Sitrat Terhadap Sifat Fisik Dan Kimia Tepung Kentang (Solanum tuberosum L.) - Lepar, Dowens Melki Eldo; Oessoe, Yoakhim Y. E.; Sumual, Maria Fransisca (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
The aim of this study was to analyze the effect of citric acid concentration on the physicochemical properties of potato starch (Solanum tuberosum L.), especially the superjon variety. This study used a completely randomized design (CRD) method which consisted of 4 treatments and 3 repetitions. In treatment P0 (citric acid concentration 0% water 1000 ml). P1 (citric acid concentration 1% water 1000 ml). P2 (citric acid concentration 2% water 1000 ml) and P3 (citric acid concentration 3% water 1000 ml). The research results were processed using ANOVA, if there was a significant difference it would be followed by a 5% LSD test. The research results obtained were pH, 3.22-5.84, color, L* 69.53-75.76, a* -2.63-0.1, b* 13.03-19.63, levels water, 8.33-12.83%, ash content, 2.17-2.67%, gelatinization temperature 70.06-72.38°C, kamba density 0.81-0.85 gr/ml. The best physicochemical characteristics of potato starch were soaked in potato tubers in a 3% citric acid solution which had a characteristic L* value of 75.76, a* value of -2.63, b* value of 18.7, water content of 8.83%, degree acid (pH) 3.22, density 0.81 g/ml, gelatinization temperature 70.06°C, and ash content 2.17%. The use of citric acid in the processing of super jhon potato starch effectively inhibits the browning reaction. The characteristics of the flour produced have a significant effect, especially at higher levels of color brightness and low moisture content.